Cytotoxicity and Autophagy Induced by Ivermectin via AMPK/mTOR Signaling Pathway in RAW264.7 Cells - Xiang Wang; Jian Wang; Ping Zhang; Cheng Zhang; Weiguo Wang; Mengqi Wu; Wenping Xu; Liming Tao; Zhong Li; Yang Zhang (Molecules, 2023)
The widespread and excessive use of ivermectin (IVM) will not only cause serious environmental pollution, but will also affect metabolism of humans and other mammals that are exposed. IVM has the characteristics of being widely distributed and slowly metabolized, which will cause potential toxicity to the body. We focused on the metabolic pathway and mechanism of toxicity of IVM on RAW264.7 cells. Colony formation and LDH detection assay showed that IVM significantly inhibited the proliferation of and induced cytotoxicity in RAW264.7 cells. Intracellular biochemical analysis using Western blotting assay showed that LC3-B and Beclin-1 were upregulated and p62 was down-regulated. The combination of confocal fluorescence, calcein-AM/CoCl2, and fluorescence probe results showed that IVM could induce the opening of the mitochondrial membrane permeability transition pore, reduce mitochondrial content, and increase lysosome content. In addition, we focused on induction of IVM in the autophagy signal pathway. The Western blotting results showed that IVM increased expression of p-AMPK and decreased p-mTOR and p-S6K expression in protein levels, indicating that IVM activated the AMPK/mTOR signaling pathway. Therefore, IVM may inhibit cell proliferation by inducing cell cycle arrest and autophagy.